Genetic variability in a population of Astyanax scabripinnis: recent bottleneck and the possible influence of individuals with B chromosomes - Limeira, Daniel Meneguello; Santos, Mateus Henrique; Mateus, Rogério Pincela; Almeida, Mara Cristina de; Artoni, Roberto Ferreira (Acta Scientiarum. Biological Sciences, 2019)
Access the genetic variability of endangered and isolated populations has become an important conservation tool. Astyanax scabripinnis is a well-known fish model for genetic studies, forming very isolated populations in headwaters. Besides that, this species frequently presents supernumerary chromosomes, which elevates the interest on genetic studies. Genetic diversity of an Astyanax scabripinnis population from the Atlantic Forest (Serra da Mantiqueira region, Brazil) was assessed with microsatellite markers for the first time. Since microsatellite markers are not described for this species, we tested markers described for a related species for transferability to A. scabripinnis. Six polymorphic loci were sufficiently reliable for population genetic analysis. We found that this population passed through a recent bottleneck because of the presence of an excess of heterozygotes, low allelic diversity, heterozygosity excess, and small effective population size. Individuals with and without B chromosomes were previously identified in this population and our study found private alleles in the individuals without B chromosomes. Furthermore, when individuals without B chromosomes were removed from the analysis, the population did not present heterozygosity excess, suggesting that the bottleneck event was driven by individuals with B chromosomes. Our results provide an insight into the value of microsatellite markers as molecular tools and is the first genetic study using molecular data of A. scabripinnis from this area.